Satisfaction with and success of employee training from a public service motivation perspective - Thaler, Julia et al (2017)
New public management requires modernization processes, including modern human resource practices, to enhance public sector performance. According to human capital theory, well-qualified and highly motivated public sector employees improve institutional performance; this study investigates the extent to which employee training as human resource practice can enhance one component of employees' public service motivation (PSM), namely public interest, and their competencies as employee outcome. We examine public interest as a mediator or a moderator of the relationship between satisfaction with employee training and the resulting competence gain. The findings indicate a positive direct effect of satisfaction with employee training on competence gains and a mediating effect of public interest. - Reproduced.
Keywords: Human resources development; Public administration; Job satisfaction; Public utilities; Motivation; Employees; Training